2015
DOI: 10.1080/17470218.2014.939667
|View full text |Cite
|
Sign up to set email alerts
|

Attribute conditioning: Changing attribute-assessments through mere pairings

Abstract: We propose Attribute Conditioning (AC) as a form of learning that refers to changes in people's assessment of stimuli's (CSs) attributes due to repeated pairing with stimuli possessing these attributes (USs). We review the available evidence and, based on this review, delineate three open questions and investigate them experimentally: a) the moderating role of CS-US similarity; b) the possibility of blocking; and c) the possibility of extinction. Five experiments conditioned health and athleticism. We measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 45 publications
3
29
0
Order By: Relevance
“…In addition, the nature of the CS seems to be of little consequence. We found robust AC effects using pictures of people, abstract shapes, and nonwords (Förderer & Unkelbach, 2011); pictures of food (Förderer & Unkelbach, 2015); and self-created brand logos (Förderer & Unkelbach, 2014). In addition, CSs are ideally neutral with respect to the US attribute for psychometric reasons (i.e., separating AC effects from regression to the mean; Fiedler & Unkelbach, 2014), although changing existing attributes should work as well (see Förderer & Unkelbach, 2016).…”
Section: The Ac Paradigmmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, the nature of the CS seems to be of little consequence. We found robust AC effects using pictures of people, abstract shapes, and nonwords (Förderer & Unkelbach, 2011); pictures of food (Förderer & Unkelbach, 2015); and self-created brand logos (Förderer & Unkelbach, 2014). In addition, CSs are ideally neutral with respect to the US attribute for psychometric reasons (i.e., separating AC effects from regression to the mean; Fiedler & Unkelbach, 2014), although changing existing attributes should work as well (see Förderer & Unkelbach, 2016).…”
Section: The Ac Paradigmmentioning
confidence: 93%
“…That is, after people observe multiple pairings of Clooney with a brand, their sexiness ratings of this brand increase (Förderer & Unkelbach, 2014). We call this effect attribute conditioning (AC; Förderer & Unkelbach, 2015). People assess stimuli’s specific attributes differently because of their pairings with other stimuli possessing these specific attributes.…”
mentioning
confidence: 99%
“…First, attribute conditioning refers to changes in a non-evaluative target feature (e.g., athleticism) as the result of pairing source and target features objects (e.g., a known athlete and an unknown person). Typically, the source feature (e.g., the fact that the athlete is known to be athletic) and target feature (e.g., the extent to which the unknown person is judged to be athletic) are identical (e.g., Förderer & Unkelbach, 2015). Second, in operant evaluative conditioning, the response is the source feature object (e.g., approaching), and the stimulus linked to the response is the target feature object (e.g., the stimulus that is repeatedly approached), the valence of the response is the source feature (e.g., the fact that approaching is positive), the valence of the stimulus linked with the response is the target feature (e.g., the liking of the stimulus that is repeatedly approached).…”
Section: Spontaneous Trait Inference and Transferencementioning
confidence: 99%
“…For instance, studies on evaluative conditioning demonstrated that the mere spatio-temporal pairing of a picture showing an unknown person with a picture showing a liked person is enough to make people evaluate the unknown person as being positive (see Hofmann, De Houwer, Perugini, Baeyens, Crombez, 2010, for a review). Also other features (e.g., the extent to which an unknown person is judged to be athletic) can be influenced by the act of pairing stimuli (e.g., presenting pictures of that person together with pictures of known athletes; Förderer & Unkelbach, 2015). In all of these conditioning studies, the features of one object (a liked person or athlete) influence judgements about the features of another object (an unknown person).…”
mentioning
confidence: 99%
“…Despite the evidence of the importance of the automatic processing pathway for regulating behavior, the majority of reviews on automatic processing tasks have been limited, focusing mainly on mental health conditions delivered in laboratory settings [ 17 , 18 , 28 - 30 ]. In addition, existing reviews have routinely included studies with children whose brain development differs from that of adults [ 31 - 33 ]; thus, a need to map the existing literature examining automatic processing pathways in digital health interventions in real-world settings among adult populations was identified [ 16 , 27 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%